2018
DOI: 10.1093/gerona/gly140
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Gait Speed and Cognitive Status in Community-Dwelling Older People: A Systematic Review and Meta-analysis

Abstract: The strength of evidence for an association between gait speed and cognition was demonstrated by the number and consistency of results, as well as quality of the studies. Identification of diagnostic markers of motor cognitive risk has led to increasing interest in the effects of interventions for prevention of gait speed loss and cognitive decline in aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
96
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(113 citation statements)
references
References 28 publications
16
96
0
1
Order By: Relevance
“…These findings survived correction for multiple testing applied within the brain structure domain, but if correction multiple testing had been applied across all study measures simultaneously, only total brain volume would have remained associated with gait speed, suggesting that findings for cortical thickness, surface area, and white matter hyperintensities, although consistent with the literature, should be treated with caution.Third, slow gait at midlife was associated with poorer neurocognitive functioning across multiple cognitive domains; there was a mean difference of 16 IQ points (>1 SD) between the slowest and fastest walkers (ie, bottom vs top quintile). These findings align with those of several studies4 of older adults showing associations of slow gait with cognitive impairment and risk of dementia.Remarkably, in our study, gait speed was associated not only with concurrent neurocognitive functioning in adulthood but also with neurocognitive functioning in early childhood. The effect sizes between participants in the slowest and fastest gait speed quintiles were far from trivial: at age 3 years, the difference in brain health was 0.62 SD Research is needed to unpack the association between childhood neurocognitive functioning and midlife gait speed.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…These findings survived correction for multiple testing applied within the brain structure domain, but if correction multiple testing had been applied across all study measures simultaneously, only total brain volume would have remained associated with gait speed, suggesting that findings for cortical thickness, surface area, and white matter hyperintensities, although consistent with the literature, should be treated with caution.Third, slow gait at midlife was associated with poorer neurocognitive functioning across multiple cognitive domains; there was a mean difference of 16 IQ points (>1 SD) between the slowest and fastest walkers (ie, bottom vs top quintile). These findings align with those of several studies4 of older adults showing associations of slow gait with cognitive impairment and risk of dementia.Remarkably, in our study, gait speed was associated not only with concurrent neurocognitive functioning in adulthood but also with neurocognitive functioning in early childhood. The effect sizes between participants in the slowest and fastest gait speed quintiles were far from trivial: at age 3 years, the difference in brain health was 0.62 SD Research is needed to unpack the association between childhood neurocognitive functioning and midlife gait speed.…”
supporting
confidence: 92%
“…1,2 Reduced gait speed is a sign of advancing age 3 ; it is associated with poorer response to rehabilitation, age-related diseases, including cardiovascular disease and dementia, and early mortality. [4][5][6] Gait speed is frequently used in geriatric settings as a quick, simple, and reliable way of estimating older patients' functional capacity. It is increasingly recognized that gait is associated with not only musculoskeletal mechanisms but also with the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an intricate interaction between motor function and cognition is now recognized. Slow gait speed is predictive of multiple adverse outcomes [1] and, although it is also impacted by conditions such as sarcopenia and physical frailty [2], it is strongly associated with prevalent and incident cognitive impairment [3]. Structural and functional brain imaging studies have shown that cognition and motor control share common brain pathways, particularly in the prefrontal and temporal areas [4].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in a recently published study from the English Longitudinal Study of Aging, both baseline gait speed and change in gait speed was associated with dementia risk over a follow up of > 10 years [10]. This follows a large body of evidence indicating the strong relationship between slow gait speed and later cognitive decline [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 95%